2014
DOI: 10.1111/1750-3841.12421
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Calcium Mobility in Alkaline‐Cooked Grounded Corn in Presence of a Magnetic Field

Abstract: It was possible to determine the free-to-link threshold concentration for calcium ions in alkaline-cooked grounded-corn kernel dough; this is near 1.5% Ca. The magnetic field allows to separate and measuring different types of ions; a model to explain the dependence of the relaxation time with the magnetic field was included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…We evaluated mitochondrial membrane potential in cultured fibroblasts from control and AD patients using TMRM (Figures 3A,B ; Brand and Nicholls, 2011 ; Vargas et al, 2014 ). No significant changes in mitochondrial potential levels were detected in patients with AD compared to age-matched controls in basal conditions (Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We evaluated mitochondrial membrane potential in cultured fibroblasts from control and AD patients using TMRM (Figures 3A,B ; Brand and Nicholls, 2011 ; Vargas et al, 2014 ). No significant changes in mitochondrial potential levels were detected in patients with AD compared to age-matched controls in basal conditions (Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, studies in AD cell models have been shown that mitochondrial potential is only affected under stressor conditions such as calcium or amyloid beta peptide (Quintanilla et al, 2012 ; Vargas et al, 2014 ). In that context, we found that in all analyzed patients showed equal levels of basal calcium (Figures 4A,B ), and after treatment with thapsigargin produced a significant increase in relative calcium levels in AD patients respect to control cells (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial potential was determined using the mitochondrial dye tetramethyl-rhodamine methyl ester (TMRM) in non-quenching mode, as described previously with modifications [32] , [36] . Mitochondrial potential levels were expressed as the average of fluorescence signal (F) per area in every image, and then subtracted by the intensity of background fluorescence (F0).…”
Section: Methodsmentioning
confidence: 99%
“…A Keithley model 2400 source-meter was used to apply 2.0 V during the 30 s prior to the sample removal; the data acquisition system was a Textronic, model TX3 apparatus. 36,37 The same procedure was repeated for all of the samples. The relaxation of the voltage signal was monitored through the determination of the ionic current; Fig.…”
Section: A Sample Preparationmentioning
confidence: 99%